TrkB activation by 7, 8‐dihydroxyflavone increases synapse AMPA subunits and ameliorates spatial memory deficits in a mouse model of Alzheimer's disease. Issue 3 (29th December 2015) - Gao, Lei; Tian, Mi; Zhao, Hong‐Yun; Xu, Qian‐Qian; Huang, Yu‐Ming; Si, Qun‐Cao; Tian, Qing; Wu, Qing‐Ming; Hu, Xia‐Min; Sun, Li‐Bo; McClintock, Shawn M.; Zeng, Yan
Abstract: We recently demonstrated that activation of tyrosine receptor kinase B (TrkB) by 7, 8‐dihydroxyflavone (7, 8‐DHF), the selective TrkB agonist, increased surface alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionic acid (AMPA) receptors (AMPARs) AMPA receptor subunit GluR1 (GluA1) subunit expression at the synapses of Fragile X Syndrome mutant mice. This present study investigated the effects of 7, 8‐DHF on both memory function and synapse structure in relation to the synapse protein level of AMPARs in the Tg2576 Alzheimer's disease (AD) mouse model. The study found that chronic oral administration of 7, 8‐DHF significantly improved spatial memory and minimized dendrite loss in the hippocampus of Tg2576 mice. A key feature of 7, 8‐DHF action was the increased expression of both GluA1 and GluA2 at synapses. Interestingly, 7, 8‐DHF had no effect on the attenuation of amyloid precursor protein or Aβ exhibiting in the Tg2576 AD brains, yet it activated the phosphorylation of TrkB receptors and its downstream signals including CaMKII, Akt, Erk1/2, and cAMP‐response element‐binding protein. Importantly, cyclotraxin B (a TrkB inhibitor), U0126 (a Ras‐ERK pathway inhibitor), Wortmannin (an Akt phosphorylation inhibitor), and KN‐93 (a CaMKII inhibitor) counteracted the enhanced expression and phosphorylation of AMPAR subunits induced by 7, 8‐DHF. Collectively, our results demonstrated that 7, 8‐DHF acted on TrkB and resolved learning and memory impairments in the absence of reduced amyloid in amyloid precursor protein transgenic mice partially through improved synaptic structure and enhanced synaptic AMPARs. The findings suggest that the application of 7, 8‐DHF may be a promising new approach to improve cognitive abilities in AD. We provided extensive data demonstrating that 7, 8‐dihydroflavone, the TrkB agonist, improved Tg2576 mice spatial memory. This improvement is correlated with a reversion to normal values of GluA1 and GluA2 AMPA receptor subunits and dendritic spines in CA1. This work suggests that 7, 8‐DHF is a suitable drug to potentiate in vivo Tropomyosin receptor kinase B (TrkB) signaling in the Alzheimer's disease mice model. Abstract : We provided extensive data demonstrating that 7, 8‐dihydroflavone, the TrkB agonist, improved Tg2576 mice spatial memory. This improvement is correlated with a reversion to normal values of GluA1 and GluA2 AMPA receptor subunits and dendritic spines in CA1. This work suggests that 7, 8‐DHF is a suitable drug to potentiate in vivo Tropomyosin receptor kinase B (TrkB) signaling in the Alzheimer's disease mice model.